Density of Langerhans Cells in Nonmelanoma Skin Cancers: A Systematic Review - Joanna Pogorzelska-Dyrbuś; Jacek C. Szepietowski (Hindawi Limited, 2020)
Langerhans cells (LCs) are bone marrow-derived dendritic cells (DCs) that represent 2-3% of the entire cell population of the human skin, known to have an ability to present antigens to T lymphocytes. Moreover, there is evidence that LCs are probably capable of inducing the local cytotoxic type T-cell-mediated response against the tumour-associated antigens. In the past two decades, a dramatic increase has been noted in the incidence of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). The purpose of this study was to critically assess the results of available studies quantitatively assessing the LCs in nonmelanoma skin cancers and try to establish a conclusion of its possible impact on their future treatment. The PubMed, EMBASE, and the Web of Science databases were searched, which returned 948 citations. After a thorough analysis of full article texts, 30 studies have been chosen, including 11 of the BCC, 12 of the SCC specimens, and 7 analysing both tumour types. There was an overall trend towards slightly higher numbers of LCs in BCC than in SCC; however, these tendencies were discrepant between the studies. We presume that such differences could be caused by various staining techniques with a broad spectrum of specificity, including anti-S100, anti-CD1a, and ATPase activity staining used for LCs identification. We hypothesise that as there is a high inconsistency between the results of the studies, as far as the densities of LCs observed in the specimens are concerned, it seems that the mechanism of the influence of LCs on the antitumoural immune response is complicated. Finally, as at present, there is a paucity of available risk scores for the recurrence or progression of BCC or SCC, the creation of classification stratifying that risk including the density of LCs could bring additional information both for the physician and the patient.